2016
DOI: 10.1089/neu.2016.4439
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Magnesium Chloride within a Polyethylene Glycol Formulation in a Porcine Model of Acute Spinal Cord Injury

Abstract: A porcine model of spinal cord injury (SCI) was used to evaluate the neuroprotective effects of magnesium chloride (MgCl) within a polyethylene glycol (PEG) formulation, called "AC105" (Acorda Therapeutics Inc., Ardsley, NY). Specifically, we tested the hypothesis that AC105 would lead to greater tissue sparing at the injury site and improved behavioral outcome when delivered in a clinically realistic time window post-injury. Four hours after contusion/compression injury, Yucatan minipigs were randomized to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…A total of 13 subjects received at least 1 infusion of AC105 or placebo, although full results have not been reported as of yet. A subsequent study of AC105 in a porcine SCI model did not find improvements in locomotor recovery or weight-supported treadmill walking [72].…”
Section: Magnesium With Polyethylene Glycolmentioning
confidence: 88%
“…A total of 13 subjects received at least 1 infusion of AC105 or placebo, although full results have not been reported as of yet. A subsequent study of AC105 in a porcine SCI model did not find improvements in locomotor recovery or weight-supported treadmill walking [72].…”
Section: Magnesium With Polyethylene Glycolmentioning
confidence: 88%
“…A recent example of the use of this pig model for testing preclinical therapies for SCI is the evaluation of magnesium chloride within a polyethylene glycol formulation, which showed promise in many rodent studies [ 12 , 16 ]. While we had previously shown this therapy to be effective at improving behavioral recovery in a rodent model of thoracic and cervical SCI [ 12 , 15 ], we found that the magnesium chloride therapy did not reproduce the same promising therapeutic benefits in our pig model, either for improving locomotor recovery or increasing spared tissue at the injury site [ 22 ]. We have also used the pig model to evaluate the effect of wholebody vibration, which is applicable to individuals who have sustained an SCI and are being transported via air or road [ 21 ].…”
Section: Applications Of the Porcine Sci Modelmentioning
confidence: 90%
“…We have used the pig model to evaluate the effects of vibration associated with transportation in ground or aircraft settings, and have taken advantage of the ability to obtain serial CSF samples to evaluate biomarkers of injury severity and surrogate outcome measures [ 20 , 21 ]. The ability to take serial CSF samples is also valuable for testing the biodistribution of drugs, as we have shown by measuring CSF levels of magnesium in a study of a magnesium chloride neuroprotective agent in the pig model [ 22 ].…”
Section: Applications Of the Porcine Sci Modelmentioning
confidence: 99%
“…This requirement generally means using small to medium sized lesions as more severe primary lesions that occupy most or all of the cross sectional area of the cord leave little surrounding undamaged tissue into which secondary expansion can occur. For example, the absence of any significant neuroprotective effect in a large animal trial of MgPEG ( Streijger et al , 2016), previously shown to be neuroprotective in rodents ( Kwon et al , 2009), is probably due to the absence of any viable tissue to protect at the injury centre. In the present study, we used controlled impacts to the exposed thoracic spinal cord to produce moderate spinal cord lesions that are initially confined to the central grey matter.…”
Section: Blood-spinal Cord Barrier Dysfunctionmentioning
confidence: 99%